STRATEGI BRANDING KOMPAS TV sebagai TELEVISI BERITA “INDEPENDEN TERPERCAYA” - Maria Elgyptya Assegaff; Agus Naryoso (Interaksi Online, 2019)
If Kompas TV wants to survive in the television industry, KompasTV is demanded to return to its essence, news. To make the maneuver, KompasTV must carry out the branding process in order to position its new image as news television. Based on the company's ideology, “Independen Terpercaya” was finally chosen by KompasTV as the tagline. This research objective is to find out the branding strategy and process carried out by KompasTV to be evaluated later. The concept of branding planning, especially in terms of strengthening brand equity as a basis for evaluating the “Independen Terpercaya” KompasTV branding. Therefore, this study uses a qualitative descriptive method with a positivistic approach. The results showed that the branding carried out by Kompas TV was in accordance with the existing branding planning concept and could be executed properly. This can be seen from Kompas TV's efforts to build the “Independen Terpercaya” Kompas TV branding both through on-air programs, events until digital media.